Cerro respiro and the inca administration in the Chillon lower valley - Ayala Castillo, Gil Ronal (2021)
This article is the result of investigations carried out at the Cerro Respiro site located on the right bank of the lower Chillón valley, very close to where the Chillón river flows. The works carried out on the site had as a corollary to give an explanation about its chronology and functionality of the site, directly related to the political-administrative organization from the buildings defined as elite residences and public spaces, whose architectural characteristics define it as such, where the excavated contexts and cultural evidences were defined to the Late Intermediate and Late Horizon period, which serve as support to the problem posed. The site is explained based on a comparative architectural analysis of three settlements that share elite residential buildings and would have performed the same function in the Chillón valley. This type of Inca facilities would have been the result of the conquest process directly, a strategy carried out by the Inca state, with the aim of controlling human, agricultural and natural resources from the elite palaces or residences located in strategic points of the valley under del Chillón, articulated to a network of roads of which there is still evidence.